2004
DOI: 10.1104/pp.103.035451
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins Repress Photomorphogenesis in Darkness

Abstract: Plants undergo two different developmental programs depending on whether they are growing in darkness (skotomorphogenesis) or in the presence of light (photomorphogenesis). It has been proposed that the latter is the default pathway followed by many plants after germination and before the seedling emerges from soil. The transition between the two pathways is tightly regulated. The conserved COP1-based complex is central in the light-dependent repression of photomorphogenesis in darkness. Besides this control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
205
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(235 citation statements)
references
References 50 publications
(54 reference statements)
18
205
0
3
Order By: Relevance
“…For instance, light was shown to promote the germination of Arabidopsis and lettuce seeds by increasing their GA content via the induction GA 3b-hydroxylases (Toyomasu et al, 1998;Yamaguchi et al, 1998). Alabadí et al (2004) reported that both mutational and chemical disruption of GA synthesis can interfere with normal skotomorphogenesis and cause aberrant expression of light-regulated nuclear genes. Furthermore, ethylene and GA were found to act coordinately in the phytochrome-mediated shade avoidance response, but their effect could be abolished by paclobutrazol, an inhibitor of GA synthesis (Pierik et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, light was shown to promote the germination of Arabidopsis and lettuce seeds by increasing their GA content via the induction GA 3b-hydroxylases (Toyomasu et al, 1998;Yamaguchi et al, 1998). Alabadí et al (2004) reported that both mutational and chemical disruption of GA synthesis can interfere with normal skotomorphogenesis and cause aberrant expression of light-regulated nuclear genes. Furthermore, ethylene and GA were found to act coordinately in the phytochrome-mediated shade avoidance response, but their effect could be abolished by paclobutrazol, an inhibitor of GA synthesis (Pierik et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Gibberellins (GAs) exert an opposite effect to light on photomorphogenesis 2 . GAs promote etiolated growth, whereas GA-deficiency induces a partially de-etiolated phenotype in the dark, which is reverted by a lack of DELLA function 2,9 . DELLAs function as key repressors of GA-responsive growth, by inhibiting GA-regulated gene expression 5 .…”
mentioning
confidence: 99%
“…Cell elongation during seedling development is antagonistically regulated by light and gibberellins (GAs) 1,2 . Light induces photomorphogenesis, leading to inhibition of hypocotyl growth, whereas GAs promote etiolated growth, characterized by increased hypocotyl elongation.…”
mentioning
confidence: 99%
“…Reed et al, 1996;Ait-ali et al, 1999;Alabadí et al, 2004), none have systematically investigated the role of DELLAs in light-mediated growth regulation. Recent advances have led to the development of Arabidopsis mutant lines that are multiply DELLA deficient and to the use of these lines in experiments that reveal the role of DELLAs in many aspects of plant growth and development, including those that are influenced by environmental conditions (Lee et al, 2002;Cheng et al, 2004;Yu et al, 2004;Cao et al, 2005;Achard et al, 2006).…”
mentioning
confidence: 99%